Associations of Insertion-deletion Polymorphism of Angiotensin-converting Enzyme with the Risk of Preeclampsia Development among Pregnant Women in Central Russia - Reshetnikov, Evgeny A. (Asian Journal of Pharmaceutics (AJP), 2017)
Objectives: The associations of the insertion-deletion angiotensin-converting enzyme (I/D ACE) genetic polymorphism with the risk of preeclampsia development were studied. Materials and Methods: The study group included 350 women: 100 women with a physiological pregnancy and 250 pregnant women with preeclampsia. All women underwent the typing of I/D polymorphism of the ACE gene. Results: The pregnant women with the preeclampsia of the 2nd degree of severity showed the lowest concentration of genotype II ACE (11.00%) as compared with pregnant women without preeclampsia (25.00%; odds ratio [OR] = 0.37; P = 0.017; Pcor = 0.051). With the preeclampsia of the 3rd degree of severity, the minimum frequency of the genotype II ACE (7.27%) and the maximum frequency of the allele D ACE (62.73%) are recorded among pregnant women as compared with the pregnant women without preeclampsia (25.00%; OR = 0.24; P = 0.01; Pcor = 0.03 and 49.50%, OR = 1.72, P = 0.03, respectively). Conclusions: Thus, the D ACE allele is associated with the risk of preeclampsia development of the 3rd degree of severity, and the ACE genotype II is a protective factor of preeclampsia development of the 2nd and the 3rd degree of severity.